Emergency cesarean section is a risk factor for depressive symptoms when breastfeeding is limited - Takács, Lea; Smolík, Filip; Lacinová, Lenka; Daňsová, Petra; Feng, Tianshu; Mudrák, Jiří; Zábrodská, Kateřina; Monk, Catherine (Journal of psychosomatic research, 2022)
OBJECTIVE: Previous studies indicated associations between cesarean section (CS), breastfeeding, and depressive symptoms. There is, however, little research integrating these variables into one model to analyze their interrelations. The aim of this observational prospective longitudinal study is to examine whether the effect of CS on postpartum depressive symptoms is mediated by difficulties with breastfeeding. METHODS: The participants were recruited in 5 maternity hospitals during their prenatal medical check-ups. Breastfeeding status was self-reported by the mothers six weeks postpartum. Screening for depressive symptoms was performed at six weeks (N = 404) and nine months (N = 234) postpartum using the Edinburgh Postnatal Depression Scale. Path analysis was used to model the relations between CS, breastfeeding, and depressive symptoms. RESULTS: No direct effects of CS on depressive symptoms at six weeks or nine months postpartum were found. CS was associated with a lower probability of exclusive breastfeeding, which was, in turn, associated with higher levels of depressive symptoms six weeks postpartum. The analysis stratified by type of CS revealed that the effect on breastfeeding only occurred with emergency, not planned, CS. The effect of CS on breastfeeding was noticeably stronger in women without versus with a history of depression. CONCLUSION: Emergency CS predicts breastfeeding difficulties, which are, in turn, associated with higher levels of depressive symptoms. Support should be provided to mothers with emergency CS and breastfeeding problems to reduce the risk of postpartum depressive symptoms in the early postpartum period.
Keywords: kojení; Pregnancy; Humans; Longitudinal Studies; poporodní období; Female; rizikové faktory; lidé; poporodní deprese; Depression, Postpartum; ženské pohlaví; longitudinální studie; Cesarean Section; těhotenství; Depression; Breast Feeding; matky; prospektivní studie; Postpartum Period; deprese; císařský řez; Mothers; Risk Factors; Prospective Studies